2022
DOI: 10.3390/cancers14174328
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant Stereotactic Radiotherapy for Brain Metastases: Systematic Review and Meta-Analysis of the Literature and Ongoing Clinical Trials

Abstract: Background: Brain metastases (BMs) carry a high morbidity and mortality burden. Neoadjuvant stereotactic radiotherapy (NaSRT) has shown promising results. We systematically reviewed the literature on NaSRT for BMs. Methods: PubMed, EMBASE, Scopus, Web-of-Science, Cochrane, and ClinicalTrial.gov were searched following the PRISMA guidelines to include studies and ongoing trials reporting NaSRT for BMs. Indications, protocols, and outcomes were analyzed using indirect random-effect meta-analyses. Results: We inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 50 publications
(105 reference statements)
0
4
0
Order By: Relevance
“…As other studies have shown the risk of radionecrosis to be dose-dependent, some therapeutic strategies using de-escalated doses and subsequent surgery (neoadjuvant SRS) or staged dosing over some weeks (staged SRS) might be safer options than definitive SRS in certain conditions. 33 , 34 In addition, since the radionecrosis risk depends on the proportion of the healthy brain tissue exposed to high radiation doses, some SRS techniques, which are characterized by greater dose conformity than that in our study, might determine better outcomes than ours. 35 - 37 However, this assumption should be addressed in specific trials.…”
Section: Discussionmentioning
confidence: 67%
“…As other studies have shown the risk of radionecrosis to be dose-dependent, some therapeutic strategies using de-escalated doses and subsequent surgery (neoadjuvant SRS) or staged dosing over some weeks (staged SRS) might be safer options than definitive SRS in certain conditions. 33 , 34 In addition, since the radionecrosis risk depends on the proportion of the healthy brain tissue exposed to high radiation doses, some SRS techniques, which are characterized by greater dose conformity than that in our study, might determine better outcomes than ours. 35 - 37 However, this assumption should be addressed in specific trials.…”
Section: Discussionmentioning
confidence: 67%
“…Lung-molGPA reportedly provides a better predictive value, suggesting that lung-molGPA can comprehensively and accurately reflect the prognosis of NSCLC complicated by brain metastases ( 24 , 28 30 ). These also suggest the importance of individualized therapy for craniocerebral radiotherapy ( 12 , 31 33 ). Moreover, most previous retrospective studies have shown that EGFR-TKI concurrently administered with radiotherapy was more effective than treatment with EGFR-TKI alone, which was not consistent with the results of our study ( 10 , 19 , 34 , 35 ).…”
Section: Discussionmentioning
confidence: 96%
“…By allowing the 3 physicians to delineate brain metastases based on the contours generated initially with our AI tool, the contouring time was reduced by 60%, with the contouring accuracy being improved. The resulting time savings could also be useful for streamlining therapeutic strategies that require timely contouring interventions, such as in neoadjuvant SRS ( 29 ). These findings suggest that our AI tool can be useful in performing single brain metastasis contouring for GK planning in clinical practice.…”
Section: Discussionmentioning
confidence: 99%